Implementasi Nilai Nilai Keislaman Dalam Pembelajaran Fiqih di MTs Mualimin Univa - Hibatullah, Rifqoh (EL-EMIR Institute, 2024)
This study aims to analyze the implementation of Islamic values in Fiqh learning at MTs Mualimin Univa and its impact on the character development of students. Islamic values such as honesty, discipline, responsibility, and noble character are essential to instill in religious education, particularly in Fiqh, which governs various aspects of Muslim life. This research uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the implementation of Islamic values in Fiqh learning at MTs Mualimin Univa is carried out through an integrative approach that connects Fiqh theory with everyday life practices. Teachers play a crucial role in guiding and providing concrete examples of applying Islamic laws in contexts relevant to students. Additionally, extracurricular religious activities, such as study circles and Qur'an memorization, also support holistic Fiqh learning.The application of Islamic values in Fiqh learning has proven effective in shaping students' religious, honest, and responsible character. This study concludes that Fiqh learning based on Islamic values not only enhances students' understanding of Islamic laws but also helps shape personalities aligned with religious teachings. It is hoped that this research can serve as a reference for developing more effective Fiqh teaching methods oriented toward strengthening Islamic character in Islamic educational institutions.